Ebv-circRPMS1 promotes the progression of EBV-associated gastric carcinoma via Sam68-dependent activation of METTL3. (1st June 2022) - Zhang, Jing-yue; Du, Yu; Gong, Li-ping; Shao, Yi-ting; Pan, Li-jie; Feng, Zhi-ying; Pan, Yu-hang; Huang, Jun-ting; Wen, Jing-yun; Sun, Li-ping; Chen, Gao-feng; Chen, Jian-ning; et al.
Abstract: Epstein–Barr virus (EBV) is a tumor virus that is associated with a variety of neoplasms, including EBV-associated gastric carcinoma (EBVaGC). Recently, EBV was reported to generate various circular RNAs (circRNAs). CircRNAs are important regulators of tumorigenesis by modulating the malignant behaviors of tumor cells. However, to date, the functions of ebv-circRNAs in EBVaGC remain poorly understood. In the present study, we observed high ebv-circRPMS1 expression in EBVaGC and showed that ebv-circRPMS1 promoted the proliferation, migration, and invasion and inhibited the apoptosis of EBVaGC cells. In addition, METTL3 was upregulated in GC cells overexpressing ebv-circRPMS1. Mechanistically, ebv-circRPMS1 bound to Sam68 to facilitate its physical interaction with the METTL3 promotor, resulting in the transactivation of METTL3 and cancer progression. In clinical EBVaGC samples, ebv-circRPMS1 was associated with distant metastasis and a poor prognosis. Based on these findings, ebv-circRPMS1 contributed to EBVaGC progression by recruiting Sam68 to the METTL3 promoter to induce METTL3 expression. ebv-circRPMS1, Sam68, and METTL3 might serve as therapeutic targets for EBVaGC. Highlights: ebv-circRPMS1 promoted the proliferation, migration, invasion, and anti-apoptosis abilities of EBVaGC cells. ebv-circRPMS1 performed its effects by recruiting the Sam68 to the promoter of METTL3 and enhancing its transcription. In clinical EBVaGC samples, ebv-circRPMS1 was associated with distant metastasis and poor prognosis.